2022
DOI: 10.1109/access.2022.3228793
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Predicts Patient Tangible Outcomes After Dental Implant Surgery

Abstract: Dental implants have become increasingly important in daily dental offices. The degree of pain and discomfort experienced during a surgical procedure varies from one patient to another. Using advanced machine learning algorithms to predict pain, the dentist and the patient would make more informed decisions about the treatment. This study aims at Predicting postoperative discomfort using an AI-based multi-linear regression model. The functional parametric association between the eight parameters (age, sex, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Regression models are a set of methods that utilize ML algorithms to automatically detect patterns and predict outcomes based on input data [35]. In the context of pain research, regression models have the potential to help the diagnosis, classification, and management of pain [36,37]. These models can predict pain occurrence, probability, volatility, and management response via a logistic regression model.…”
Section: J Biomed Phys Engmentioning
confidence: 99%
See 1 more Smart Citation
“…Regression models are a set of methods that utilize ML algorithms to automatically detect patterns and predict outcomes based on input data [35]. In the context of pain research, regression models have the potential to help the diagnosis, classification, and management of pain [36,37]. These models can predict pain occurrence, probability, volatility, and management response via a logistic regression model.…”
Section: J Biomed Phys Engmentioning
confidence: 99%
“…Several studies have demonstrated the potential of regression models in pain research [37][38][39][40][41], with successful predictions of imaging no-shows, pain severity in patients with primary Sjögren syndrome [39] or juvenile idiopathic arthritis [40], and postoperative discomfort following implant surgery [37].…”
Section: J Biomed Phys Engmentioning
confidence: 99%
“…Artificial intelligence (A.I.) [6][7][8][9][10][11][12], which imitates human cognitive processes, is a revolutionary technology that has captured the attention of scientists worldwide [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Background and Introductionmentioning
confidence: 99%
“…In the contemporary field of dentistry, numerous studies have embraced the integration of digital technologies. Technologies such as cone beam computed tomography (CBCT) imaging [6], surgical guides [7], robotic navigation systems for surgery [8], and even the incorporation of AI in surgery [9] have collectively optimized dental procedures, rendering them more comprehensive and precise. Traditionally, digital panoramic radiography (DPR) has been used to image periodontal conditions and take manual impressions, a process prone to human error.…”
Section: Introductionmentioning
confidence: 99%